Commitment Of Small Business Actors To Shopee Online Consumers - Mery Ramadani; Sutikno Sutikno (Fakultas Bisnis, 2021)
Small business actors experience complaints from customers about services, products, and prices sold. The purpose of the study was to determine the effect of services, products, and prices on the commitment of small business actors to Shopee online consumers in 2020. The data was obtained by distributing online questionnaires via Google Form to 350 Shopee online consumers. This research technique takes a sample using non-probability sampling with the method used in this study is the Structural Equation Model technique. The results of the study prove that there is a positive and significant influence of services, products, and prices where consumers place their trust in small business actors in online shopee positively affecting seller commitment